O-GlcNAcylation of Sox2 at threonine 258 regulates the self-renewal and early cell fate of embryonic stem cells - Kim, Dong Keon; Lee, Jang-Seok; Lee, Eun Young; Jang, Hansol; Han, Suji; Kim, Hee Yeon; Hwang, In-Young; Choi, Ji-Woong; Shin, Hyun Mu; You, Hye Jin; Youn, Hong-Duk; Jang, Hyonchol (Experimental & molecular medicine, 2021)
Sox2 is a core transcription factor in embryonic stem cells (ESCs), and O -GlcNAcylation is a type of post-translational modification of nuclear-cytoplasmic proteins. Although both factors play important roles in the maintenance and differentiation of ESCs and the serine 248 (S248) and threonine 258 (T258) residues of Sox2 are modified by O -GlcNAcylation, the function of Sox2 O -GlcNAcylation is unclear. Here, we show that O -GlcNAcylation of Sox2 at T258 regulates mouse ESC self-renewal and early cell fate. ESCs in which wild-type Sox2 was replaced with the Sox2 T258A mutant exhibited reduced self-renewal, whereas ESCs with the Sox2 S248A point mutation did not. ESCs with the Sox2 T258A mutation heterologously introduced using the CRISPR/Cas9 system, designated E14-Sox2 TA/WT , also exhibited reduced self-renewal. RNA sequencing analysis under self-renewal conditions showed that upregulated expression of early differentiation genes, rather than a downregulated expression of self-renewal genes, was responsible for the reduced self-renewal of E14-Sox2 TA/WT cells. There was a significant decrease in ectodermal tissue and a marked increase in cartilage tissue in E14-Sox2 TA/WT -derived teratomas compared with normal E14 ESC-derived teratomas. RNA sequencing of teratomas revealed that genes related to brain development had generally downregulated expression in the E14-Sox2 TA/WT -derived teratomas. Our findings using the Sox2 T258A mutant suggest that Sox2 T258 O -GlcNAc has a positive effect on ESC self-renewal and plays an important role in the proper development of ectodermal lineage cells. Overall, our study directly links O -GlcNAcylation and early cell fate decisions. Stem cell development: hold the sugar Cells that can grow into any type of cell, called embryonic stem cells (ESCs), are signaled to stay in stem cell mode (maintain stemness) by addition of a single sugar molecule to Sox2, a regulatory protein coded for by a developmental gene. Sugar modification of Sox2 was known to be involved in maintaining stemness and sometimes implicated in cancer, but the mechanism was poorly understood. When Hyonchol Jang at the National Cancer Center in South Korea and co-workers prevented sugar modification of Sox2 by changing an amino acid at the sugar-binding site, ESCs showed reduced self-renewal. Rather than repressing genes related to stemness, the modification failed to repress developmental genes, permitting cells to grow into other cell types. These results illuminate both the role of Sox2 in cancer and the importance of sugar modification in stemness.